Aplikasi Human Resource Information System dengan Fitur Sistem Pendukung Keputusan (Studi Kasus PT. Industri Kreatif Digital) - Cynthia Stefanie Suriady; Lily Puspa Dewi; Alexander Setiawan (Jurnal Infra, 2021)
PT. Industri Kreatif Digital is a service company providing services for cloud hosting, VPS, and website creation. Right now, data processing for human resources still has a lot of weaknesses. One of these weaknesses is that the company still does manual work to register, payroll, collect absence, and recruitment of workers that can cause inaccuracies in processing information. PT. IKADA needs a Human Resource Information System (HRIS) that can provide simultaneous and easy processing of workers data to produce accurate and quick results. HRIS is equipped with a Decision Support System that can give out recommendations for prospective workers, promotions, and Mikrotik training for workers.In this thesis an HRIS has been designed and equipped with a few modules including personalia, recruitment, payroll, absence, evaluation, and reporting module. The Decision Support System itself uses the PIPRECIA method in calculating the weight of each criterion and uses the EDAS method in the ranking process. The system created was website-based that uses PHP framework Laravel, Javascript, HTML, and MySQL database.The result of this research is a system that can help HRD in processing workers data such as data about workers leave and overtime, recruitment, payroll, absence, workers evaluation, and reporting. On the other hand, the Decision Support System was able to provide recommendations for prospective workers, promotions, and Mikrotik training for workers based on its calculations.